(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the development trends, intellectual structure, and main thematic directions of scientific research on inclusive entrepreneurship for persons with disabilities using a bibliometric approach. The analysis is based on materials published in the field of business and economics between 2000 and 2025 and indexed in the Scopus database, and it is conducted with the support of the R software. Indicators of scientific productivity, country-level activity, co-occurrence of keywords, and thematic mapping are used to identify the key characteristics of the scientific field of inclusive entrepreneurship.